Estudo da influência do ângulo de hélice em brocas de metal duro na furação de alumínio aeronáutico - Buzinari, Ricardo Aparecido (2022)
The use in machining aluminum alloys offers many advantages: high cutting speed, low cutting forces, minimal tool wear and relatively low machining temperature. When machining aluminum alloys, it is always advisable to use tools with geometric configurations specifically designed for this application. With the tool properly configured, we were able to obtain a final hole within the tolerance, finish, and cylindricity required by the machined product. According to such purposes, studies aimed at the application of appropriate propeller angles and associated with coherent cutting parameters for machining aluminum, are necessary to obtain a hole with the proper quality required by the product or process. Thus, in this work, a study was carried out on the variation of propeller angles of 20º, 30º and 40º associated with variations in the cutting speed and feed parameters in the machining of 7475 aeronautical aluminum specimens, a material that is most used in production processes of the aerospace industry. In order to obtain the results, the specimens were duly monitored and monitored hole by hole, with the aforementioned variations for the proper collection of data in relation to the change in the helix angle and cutting parameters, where the variation of vibration can also be observed. of the applied workpiece and tool set. The results indicated that the holes obtained with the angles of 20° and 40° presented variations in the values of their diameters that are not admissible in the aeronautical sector, due to the quality requirements that aim to promote the safety of the manufactured aircraft. The 30° angle proved to be the most suitable for the drilling operation, as it provided greater dimensional control of the holes and absence of burrs in the machining, which contributes to a good internal finish of the holes.